Comparison of Laparoscopic Transabdominal Preperitoneal Mesh Repair and Open Inguinal Hernia Repair in Terms of Post-operative Pain and Hospital Stay - Hussain, Shabbir; Nazir, Aamna; Khan, Muhammad Atif; Amir, Asad (Indus Journal of Bioscience Research, 2025)
Background: Inguinal hernias occur in 0.5% to 15% of cases, with factors like location, type, and surgical technique influencing outcomes. This study compares postoperative pain (VAS) and hospital stay duration between laparoscopic trans-abdominal pre-peritoneal (TAPP) mesh repair and open mesh repair for inguinal hernia treatment. Methods: A six-month Randomised Controlled Trial, from January 2024 to June 2024 was conducted at Holy Family Hospital, Rawalpindi, involving 90 patients (45 in each group). This Randomised Controlled Trial, conducted at Holy Family Hospital, included patients aged 18-55 with inguinal hernias. It compared post-operative pain and hospital stay between two surgical approaches (open mesh repair for inguinal hernia versus laparoscopic trans-abdominal pre-peritoneal (TAPP) mesh repair) using VAS scores. Results: Results showed that the mean VAS pain scores at 12, 24, and 72 hours were significantly lower in the TAPP group compared to the open repair group. The mean hospital stay was also significantly shorter in the TAPP group (36.8 ± 5.1 hours) compared to the open repair group (42.7 ± 4.1 hours). Postoperative complications were more frequent in the open repair group, with seroma being the most common. Conclusion: While the TAPP technique had a longer operative time, it demonstrated reduced postoperative pain and shorter recovery times. These findings suggest that TAPP may be a preferable option for inguinal hernia repair, though further studies with longer follow-up are necessary to assess long-term outcomes.